Diplomatic protection and xenophobic violence in South Africa : the case for reparation to Mozambican victims - Onoria, Henry (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.